2021
DOI: 10.3389/fmed.2021.629741
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in a Cohort of 66 Patients With Psoriatic Arthritis Mutilans—Results From the Nordic PAM Study

Abstract: Objective: Psoriatic arthritis mutilans (PAM) is the most severe phenotype of psoriatic arthritis due to excessive bone erosion causing joint destruction and decreased functional capacity. The aim of this study was to investigate the prevalence of comorbidities among patients with PAM and the association between comorbidities and joint involvement.Methods: A total of 66 patients aged ≥18 years from the Nordic countries with past or present psoriasis along with at least one mutilated joint were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In this study, genomic DNA was isolated from peripheral blood mononuclear cells (PBMCs) from the Nordic PAM patient's cohort of 61 well-characterized patients previously described 4,6,7,10,11,24 . The cohort consists of patients from Sweden (n=27), Denmark (n=21), Norway (n=10), and Iceland (n=3).…”
Section: Human Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, genomic DNA was isolated from peripheral blood mononuclear cells (PBMCs) from the Nordic PAM patient's cohort of 61 well-characterized patients previously described 4,6,7,10,11,24 . The cohort consists of patients from Sweden (n=27), Denmark (n=21), Norway (n=10), and Iceland (n=3).…”
Section: Human Samplesmentioning
confidence: 99%
“…Even though the overall prevalence of PAM is uncertain, several case studies have reported on PAM patients in different populations 5, [7][8][9] , and in a Nordic PAM study it was estimated to have a prevalence of 3.7 cases per million habitants 6 . Clinical and radiographic details of patients in the Nordic PAM study have been described 4,6,7,10,11 .…”
Section: Introductionmentioning
confidence: 99%